Amyand’s Hernia: an Up-to-Date Review of the Literature - Dimitrios Patoulias; Maria Kalogirou; Ioannis Patoulias (Acta Medica, 2018)
Amyand’s hernia is defined as an inguinal hernia, containing the appendix within the hernia sac. Incidence of this rare condition rises up to 1% (0.19–1.7%) of all inguinal hernia cases. Inflammation of the appendix within the inguinal sac is even rarer, as it corresponds to 0.1% (0.07–0.13%) of all Amyand’s hernia cases. After a comprehensive review of the limited relevant literature, we aim through this review study to describe the pathophysiology of inflammation of the appendix – contained in the hernia sac – and present the latest data about the diagnostic approach and surgical treatment of Amyand’s hernia.